2010
DOI: 10.1128/jvi.01081-10
|View full text |Cite
|
Sign up to set email alerts
|

Papillomavirus Infection Requires γ Secretase

Abstract: The mechanism by which papillomaviruses breach cellular membranes to deliver their genomic cargo to the nucleus is poorly understood. Here, we show that infection by a broad range of papillomavirus types requires the intramembrane protease ␥ secretase. The ␥-secretase inhibitor (S, The necessary causal association of persistent infection by an "oncogenic" type of human papillomavirus (HPV) with cervical cancer is firmly established (52,53). HPV is the most prevalent sexually transmitted infection, and although… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
58
0
1

Year Published

2011
2011
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(67 citation statements)
references
References 53 publications
8
58
0
1
Order By: Relevance
“…However, some of the hits-furin, the γ-secretase complex, and the vacuolar ATPase complex (which causes endosome acidification)-were reported by others to be required for HPV infection or are consistent with our prior understanding of this process (17)(18)(19)(20). The identification of these genes validated our screen design and suggested that our findings were relevant to HPV16 infection.…”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…However, some of the hits-furin, the γ-secretase complex, and the vacuolar ATPase complex (which causes endosome acidification)-were reported by others to be required for HPV infection or are consistent with our prior understanding of this process (17)(18)(19)(20). The identification of these genes validated our screen design and suggested that our findings were relevant to HPV16 infection.…”
Section: Resultssupporting
confidence: 72%
“…HPV is then thought to be transferred to an as-yetunidentified cell-surface receptor, followed by endocytosis and intracellular trafficking (8)(9)(10)(11)(12)(13)(14)(15). Cyclophilin B and the proteases furin and γ-secretase play essential but not clearly understood roles during HPV entry (16)(17)(18)(19). After HPV is internalized, capsid disassembly is initiated in the endosome by acidification (11,15,20).…”
mentioning
confidence: 99%
“…Before we investigated the defect of these mutant PsVs in more detail, we tested whether the mutant viruses follow the same internalization pathway as wt HPV16. To test this, HeLa cells were infected with wt and mutant PsVs in the presence of well-established inhibitors of HPV16 infection targeting CyPs, ␥-secretase, tyrosine kinases, and endosomal acidification and trafficking (38,46,(48)(49)(50)(51)(52)(53)). All mutant PsVs tested displayed the same inhibition profile as wt HPV16 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A55 is predicted to be the most deleterious mutation, disturbing all the TM domain GxxxG motifs. A60 preserves the 52 GxxxG 56 motif but disrupts all downstream motifs, and A64 disrupts only the C-terminal 61 GxxxG 65 and 63 GxxxG 67 motifs. The A55 mutant was completely noninfectious, the A60 mutant had drastically reduced infectivity, and the A64 mutant had no reduction in infectivity (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Lastly, the intramembrane protease complex, ␥-secretase, has been shown to be absolutely critical for HPV infection (61). Biochemical inhibition of ␥-secretase potently blocks HPV16 infection, again by preventing the endosomal translocation of vDNA.…”
Section: Discussionmentioning
confidence: 99%